185 Baricitinib-associated changes in type I interferon gene signature during a 24-week phase 2 clinical SLE trial. (April 2019) - Dörner, Thomas; Tanaka, Yoshiya; Petri, Michelle; Smolen, Josef S; Dow, Ernst R; Higgs, Richard E; Benschop, Robert J; Abel, Adam; Silk, Maria E; Bono, Stephanie de; Hoffman, Robert W
Abstract : Background: In the phase 2 study JAHH (NCT02708095 ), treatment with baricitinib, an oral selective Janus kinase 1/2 inhibitor approved for the treatment of rheumatoid arthritis, resulted in significant improvements in patients with active SLE receiving standard background therapy compared with placebo. 1 Expression of type I-associated interferon (IFN) responsive genes (IRGs) is elevated in patients with SLE. 2 We developed a robust quantitative assay to measure changes in the IFN signature, and examined the relationship between the IFN signature and measures of clinical outcome. Methods: 314 patients were randomized 1:1:1 to receive placebo, baricitinib 2- or 4 mg once daily for 24 weeks in study JAHH. Total RNA isolated from whole blood was analyzed using a multiplex assay panel of 6 IRGs at baseline, and Weeks 2, 12, and 24. The assay was developed and optimized using RNA samples from 1760 patients with SLE enrolled in phase 3 trials of tabalumab (an anti-B cell activating factor monoclonal antibody), (2) along with healthy controls. The IFN signature assay produced a bimodal distribution. Results: 70% of patients had an elevated IFN signature at baseline. Baricitinib significantly reduced the IFN signature by Week 24 compared with placebo (2 mg:−20%, 4 mg:−24%, p0.05), with decreases observed as early as Week 2. In patients who had a high IFN signature at baseline, baricitinib 4 mg significantly reduced the IFN signature at Weeks 12 (-24%) and 24 (-23%) compared with placebo (p0.01); decreases were also observed at Weeks 12 and 24 with baricitinib 2 mg, but the difference from placebo was not statistically significant. Baricitinib 4 mg treatment resulted in significant clinical improvement in the resolution of arthritis or rash determined by the SLEDAI-2K. 1 However, the effect of baricitinib on IFN signature reduction (change from baseline and absolute baseline value) did not correlate with SLEDAI-2K-defined clinical improvement at Week 12 or 24. Conclusions: A dose-dependent decrease in the IFN signature was observed in baricitinib-treated patients with SLE. Baricitinib treatment resulted in clinical improvement across various measures of SLE disease activity. 1 Response was observed with baricitinib regardless of the change in the IFN gene signature. These data suggest that the clinical improvement observed in baricitinib-treated patients with SLE may be the result of baricitinib-mediated effects on multiple cytokine pathways that may include, but are not limited to, IFN signaling. Ongoing studies using gene arrays are now surveying global immune pathways to better characterize the mechanism of action of baricitinib in SLE. Funding Source(s): Eli Lilly and Company References: Wallace, D. et al . DOI:10.1136/annrheumdis-2018-eular.1918 Hoffman, W. et al. Arthritis Rheumatol 2017;69:643–654.